2015
DOI: 10.1007/978-1-4939-2113-3
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing Technologies

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
449
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,884 publications
(523 citation statements)
references
References 4 publications
1
449
0
16
Order By: Relevance
“…Near-net-shape components using additive manufacturing (AM or 3D printing) and powder metallurgy (PM) methods have recently been used to alleviate some of these cost problems (Ref [1][2][3]. AM of metals can be separated into two broad categories: indirect methods, where a binder is used to bond the metal particles and post-processing is used to remove the binder and consolidate the part, and direct methods, where the final part is created directly without a binder (Ref 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-net-shape components using additive manufacturing (AM or 3D printing) and powder metallurgy (PM) methods have recently been used to alleviate some of these cost problems (Ref [1][2][3]. AM of metals can be separated into two broad categories: indirect methods, where a binder is used to bond the metal particles and post-processing is used to remove the binder and consolidate the part, and direct methods, where the final part is created directly without a binder (Ref 4).…”
Section: Introductionmentioning
confidence: 99%
“…AM of metals can be separated into two broad categories: indirect methods, where a binder is used to bond the metal particles and post-processing is used to remove the binder and consolidate the part, and direct methods, where the final part is created directly without a binder (Ref 4). It is possible to fabricate intricate parts with good surface finishes with processes such as electron beam melting (EBM) (Ref [3][4][5]; however, this process is currently limited by a manufacturing rate of 6 g/ min at the very high end for titanium [modified from (Ref 6, 7) using a density of titanium of 4.51 g/cm 2 ( Ref 1)]. This deposition rate leaves much room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two years, there have been three review papers seeking to explore this topic and collate findings in this emerging field (Gibson et al 2015;Kumke, Watschke, and Vietor 2016;. Gibson et al (2015) reviewed the recent advances in DfAM and identified the advantages of AM in producing complex geometry, integrated assemblies, customised geometry, multi-functional products and lightweight structures.…”
Section: Design For Additive Manufacturing (Dfam)mentioning
confidence: 99%
“…Gibson et al (2015) reviewed the recent advances in DfAM and identified the advantages of AM in producing complex geometry, integrated assemblies, customised geometry, multi-functional products and lightweight structures. presented a systematic review of literature on DfAM.…”
Section: Design For Additive Manufacturing (Dfam)mentioning
confidence: 99%
“…Several other terms are, or used to be, in use as well: automated fabrication, freeform fabrication or solid freeform fabrication, layer-based manufacturing, stereo li thography or 3D printing [1]. There are numerous ways to classify AM technologies, but recently accepted ISO/ASTM 52900 standard [2] classifies AM processes regarding type of material, principle applied for fusion or bonding, feedstock that is used for adding the material and machine architecture, i.e.…”
Section: Introductionmentioning
confidence: 99%